2022
DOI: 10.21608/ejhm.2022.212028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Contractile Recovery After Successful Primary Percutaneous Coronary Intervention

Abstract: Background: Accurate diagnosis, characterization, and quantification of myocardial infarction (MI) are essential to assess the impact of therapy and to aid in predicting prognosis of patients with ischaemic heart disease.Objective: This study aimed to define different parameters regarding prediction of myocardial functional recovery following successful reperfusion of acute ST segment elevation myocardial infarction (STEMI). Patients and methods: This prospective study was carried out in Zagazig University and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…This was consistent with other studies. 14 , 17 , 18 Also, there was a statistically significant difference between the study groups regarding baseline LV- EDV as the group improving LVEF post PCI had smaller values and this is similar to other studies. 14 , 19 This all could be explained by the severity/extension of myocardial injury (reflected by an elevated level of serum troponin) and the degree of LV remodeling (dilatation) during the acute ischemic phase both hindering LV improvement and further recovery even after successful revascularization.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This was consistent with other studies. 14 , 17 , 18 Also, there was a statistically significant difference between the study groups regarding baseline LV- EDV as the group improving LVEF post PCI had smaller values and this is similar to other studies. 14 , 19 This all could be explained by the severity/extension of myocardial injury (reflected by an elevated level of serum troponin) and the degree of LV remodeling (dilatation) during the acute ischemic phase both hindering LV improvement and further recovery even after successful revascularization.…”
Section: Discussionsupporting
confidence: 88%
“…They mostly suggested a GLS lower than about 12%–15% to be a significant independent predictor of adverse outcomes. 14 , 26 , 27 Our results showed that a GLS- cut-off value of greater than 9%; predicts further LV recovery and this relatively differs from other reported values among similar studies. Many factors might be attributed to this finding; the mean age of our patients is slightly older compared to other studies, variable types of ACS presentation, lower mean LVEF at the acute insult, and a larger sample of the population with a variable background.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation